Ethnobotanical Study In The Traditional Mangrara Banua Ceremony Of Tongkonan Toraja - Willy Yavet Tandirerung; Adewidar Marano Pata’dungan; Berlian Zetikarya Haryati; Vonnisye Vonnisye (Jurnal Info Sains : Informatika dan Sains, 2023)
One of the traditional rituals performed by the Toraja community, the Mangrara Banua ceremonial, involves the use of plants. The Tongkonan House, the Toraja tribe's traditional house, holds an annual celebration of thankfulness known as the Banua Mangrara. The goal of this ethnobotany study is to identify the kinds of plants that the Toraja people employ in their Banua Mangrara rite. The Mangrara Banua Tongkonan Randan Aya' Bebo's, the Northern Sangalla District, and the Banua Tungkonan Tok Serrek, Maruang Batu Rongko, Sopai District were the locations of the research from November 2022 to April 2023. Observations, interviews, and documentation are used to gather data. Purposive sampling and snowball sampling are used to choose respondents. Utilizing qualitative descriptive analysis, the data was examined. According to research, the Mangrara Banua Tongkonan ceremony of the Toraja tribe uses 23 species of plants from 15 families that are significant. Different roles for these plant species are played during the course of traditional ceremonies. The organs of plants that are most commonly used in this traditional ceremony are the leaves and stems, while certain species also use the fruit and umbilia. The plants used in these traditional ceremonies cannot be changed because they are an ancestor's tradition. Therefore, in an effort to protect the plants, the Toraja community is pursuing planting operations in the fields surrounding Tongkonan houses and gardens.